PELATIHAN SENI BATIK TULIS BAGI GURU-GURU MGMP SENIBUDAYA SMP SE-KABUPATEN GUNUNGKIDUL - dan Ismadi, Muhajirin, Iswahyudi, (Universitas Negeri Yogyakarta, 2012)
The Training of batik aims to provide skills in the making of batikand to enrich the matter of art and culture lesson for the teachers of JurnalHigh School in Gunungkidul. The ability and conpetence in making batikthat mastered by teachers are expected to trigger students's interest for themore enthusiastic in following the batik lesson, and ultimately will improvethe overall quality of the learning of art and cukture.The method that is applied on this activity is the method ofpresentation of the matter of batik, including the matter about history ofbatik, tools and material in making the batik. The method of demonstrationincluding the making of design, and the procedures of the making of batikfrom beginning to end. The method of evaluation is by examining thedifferences in the ability of teachers before and after training.The results shown a significant improvement compared beforetraining, so it can be concluded that this activity improved the ability of theparticipants. The evaluation of the results seen from the assessment tasksthat illustrate the successful practice of material that has been presented. Italso examined the performance and participation of the participants. At theend of the program the team captured meaningful data from theparticipants. It is expected that this training program continues because ofits advantages to improve the quality of the learning of art and culture lessonin Jurnal High School..